When caregivers are in need of care: African American caregivers’ preferences for their own later life care - Anderson, Jared R.; Turner, William L. (My University, 2013)
To “care for one's own” is a cultural expectation within a larger ethic of care in the African-American community. Applied to caregiving of aging elders, this ethic of care emphasizes the importance of providing in-home family care rather than opting for out-of-home placement. This study explores why a subset of African-American caregivers prefer or are open to out-of-home placement over in-home family care if they are no longer able to care for themselves. In-depth interviews with 24 family caregivers are analyzed. Three themes emerged including the desire to “spare our children” the burden associated with caregiving, viewing the next generation of potential caregivers as unequipped for the task, and having no one left to provide care for them.
Keywords: Later life care; African American caregivers; Decision making